‫أثر الأداء‬ ‫المالي‬ ‫و‬ ‫البورصوي‬ ‫على‬ ‫قرار‬ ‫فتح‬ ‫رأس‬ ‫المال‬ ‫دراسة‬‫حالة‬ ‫مؤسسة‬ ‫بيوفارم‬ ‫خلال‬ ‫الفترة‬‫‪2013‬‬‫‪-‬‬‫‪2016‫)‬ - ‬‫محمد ‫عفاري ‬; علي‬ ‫أولقيمة‬‫ (My University, 2018)
The company aims to rationalize its financial decisions in order to build a financial structure which helps progress and development towards the better, and this in opening its capital to subscription, the aim of this study is to research the impact financial and stock market performance on the decision to open the capital of the Enterprise biopharm in the know (2013-2016) by adopting the descriptive approach and analytical through the evaluation of financial and stock market performance based on on the different indicators adopted in the study. This study ended up revealing the presence of a large impact of performance financial and stock market on the opening of the capital as a tool for evaluating the level of the Enterprise. the study advised the imperative of continuous evaluation of the performance in order to benefit from its results and improve it at the stock market level, in order to achieve the expected goals and encourage investors to carry out operations and stock market transactions including the opening of capital. .................................................................. وتهدف الشركة إلى ترشيد قراراتها المالية من أجل بناء الهيكل المالي الذي يساعد على التقدم والتطور نحو الأفضل، وهذا في فتح رأس مالها للاكتتاب، والهدف من هذه الدراسة هو البحث في الأثر أداء الأسواق المالية والبورصة بشأن قرار فتح رأس المال المؤسسة الصيدلانية الحيوية في المعرفة (2013-2016) باعتماد المنهج الوصفي و التحليلية من خلال تقييم الأداء المالي وأسواق الأوراق المالية على أساس على المؤشرات المختلفة المعتمدة في الدراسة. وانتهت هذه الدراسة بالكشف عن وجود تأثير كبير للأداء المالية وسوق الأوراق المالية على افتتاح رأس المال كأداة لتقييم المستوى المؤسسة. ونصحت الدراسة بضرورة التقييم المستمر للحالة الأداء للاستفادة من نتائجه وتحسينه على مستوى سوق الأوراق المالية، وذلك لتحقيق الأهداف المتوقعة وتشجيع المستثمرين على القيام بعمليات و معاملات سوق الأوراق المالية بما في ذلك فتح رأس المال.